解方程3分之x-2=2分之x-3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 06:20:15
解方程3分之x-2=2分之x-3解方程3分之x-2=2分之x-3解方程3分之x-2=2分之x-3(x-2)/3=(x-3)/22x-4=3x-9x=5等式互换得:3X-9=2X-4X=5
解方程3分之x-2=2分之x-3
解方程3分之x-2=2分之x-3
解方程3分之x-2=2分之x-3
(x-2)/3=(x-3)/2
2x-4=3x-9
x=5
等式互换得:
3X-9=2X-4
X=5
解方程:2分之x-3分之x=5
2分之x-3分之x=6 解方程
解方程(:x-3分之x)+(x^2-3x分之x+6)=x分之x-3
解方程:3分之2X+4分之1X=3分之2 求X
解方程3分之2+3x-1分之x=9x-3分之1
解分式方程 2x-4分之3+2-x分之x=2分之1
解方程(:x分之2)-(x-1分之1)=(2x-2分之3)
0.6x+5分之2x-7分之3x=3分之4解方程
解方程1*2分之x+2*3分之x+...+2010*2011分之x=2010
解方程1×2分之x+2×3分之x+...+2010×2011分之x=2010
解方程:1*2分之x+2*3分之x+.+2011*2012分之x=2011
解方程1+x分之2-1-x分之3=x-1分之6
解方程:X+7分之2X=4分之3 X-5分之4X=10分之3
解方程x+2分之x-2 + x平方-4分之4x =x-2分之x+3
解方程:7分之X+3-5分之X+2=6分之X+6-4分之X+4
1X2分之X+2X3分之X+3X4分之X+.+2010X2011分之X=2010 解方程
解方程(2-x分之x-1)-1=x-2分之3分式方程解法
x-15分之2=3分之2解方程